Implicative Ideals of BCK-Algebras Based on the Fuzzy Sets and the Theory of Falling Shadows - Young Bae Jun; Min Su Kang; Chul Hwan Park (International Journal of Mathematics and Mathematical Sciences)
Based on the theory of falling shadows and fuzzy sets, the notion of a falling fuzzy implicative ideal of a BCK-algebra is introduced. Relations among falling fuzzy ideals, falling fuzzy implicative ideals, falling fuzzy positive implicative ideals, and falling fuzzy commutative ideals are given. Relations between fuzzy implicative ideals and falling fuzzy implicative ideals are provided.